A novel method of preparing Ti powder for 3D printing. Issue 6 (13th August 2018) - Zhang, Yajuan; Song, Xiaoyan; Wang, Haibin; Nie, Zuoren
Abstract : Purpose: The purpose of this paper is to propose a novel method to prepare pure Ti powder for 3D printing with tailorable particle size distribution. Design/methodology/approach: The main procedures of the present method consist of gas state reaction to synthesize TiH2 nanoparticles, agglomeration to obtain micronscale powder particles by spray drying, and densification of particle interior by heat treatment. Findings: The prepared Ti powder has a specific bimodal particle size distribution in a range of small sizes, good sphericity and high flowability. Particularly, this new technique is capable of controlling powder purity and adjusting particle size. Originality/value: To the best knowledge of the authors, the approach for preparing 3D printing metallic powders from nanoparticles has not been reported in the literature so far. This work provides a novel method that is particularly applicable to prepare 3D printing metallic powders which have small initial particle sizes and high reactivity in the air.